2022
DOI: 10.1097/qad.0000000000003344
|View full text |Cite
|
Sign up to set email alerts
|

Diet in a global cohort of adults with HIV at low-to-moderate traditional cardiovascular disease risk

Abstract: Objective:To characterize diet quality across a global cohort of people with HIV (PWH).Design:Cross-sectional analysis.Methods:Leveraging REPRIEVE data from baseline across five Global Burden of Disease (GBD) regions, we analyzed participant responses to the Rapid Eating Assessment for Participants questionnaire. An overall diet quality score and scores for specific diet components were generated. Higher scores indicate better diet quality.Results:Among 7736 participants (median age 50 years, 30% women, median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“… 41 Patients with higher ASCVD risk were more likely to be older; men; smokers; hypertensive; of African ancestry; and have higher triglyceride and glucose concentrations and lower HDL‐C, CD4 count, and estimated glomerular filtration rate. 42 There were no differences in physical activity, body mass index, and LDL‐C concentration at the time of enrollment among patients in different ASCVD risk tertiles.…”
Section: Resultsmentioning
confidence: 86%
“… 41 Patients with higher ASCVD risk were more likely to be older; men; smokers; hypertensive; of African ancestry; and have higher triglyceride and glucose concentrations and lower HDL‐C, CD4 count, and estimated glomerular filtration rate. 42 There were no differences in physical activity, body mass index, and LDL‐C concentration at the time of enrollment among patients in different ASCVD risk tertiles.…”
Section: Resultsmentioning
confidence: 86%
“… 76 The REPRIEVE study of cardiovascular health, for example, found that more than 60% had optimal diet in South Asia, whereas only 6% did in sub-Saharan Africa. 77 The literature on interventions to address food insecurity is mixed. 78 Regarding housing, as of 2016, it was estimated that greater then 10% of PWH of all ages had unmet housing needs.…”
Section: Components Of Carementioning
confidence: 99%